An economic evaluation of planned immediate versus delayed birth for preterm prelabour rupture of membranes: findings from the PPROMT randomised controlled trial. (21st October 2016) - Lain, SJ; Roberts, CL; Bond, DM; Smith, J; Morris, JM
Abstract : Objective: This study is an economic evaluation of immediate birth compared with expectant management in women with preterm prelabour rupture of the membranes near term (PPROMT). Design: A cost‐effectiveness analysis alongside the PPROMT randomised controlled trial. Setting: Obstetric departments in 65 hospitals across 11 countries. Population: Women with a singleton pregnancy with ruptured membranes between 34 +0 and 36 +6 weeks gestation. Methods: Women were randomly allocated to immediate birth or expectant management. Costs to the health system were identified and valued. National hospital costing data from both the UK and Australia were used. Average cost per recruit in each arm was calculated and 95% confidence intervals were estimated using bootstrap re‐sampling. Averages costs during antenatal care, delivery and postnatal care, and by country were estimated. Main outcomes measures: Total mean cost difference between immediate birth and expectant management arms of the trial. Results: From 11 countries 923 women were randomised to immediate birth and 912 were randomised to expectant management. Total mean costs per recruit were £8852 for immediate birth and £8740 for expectant delivery resulting in a mean difference in costs of £112 (95% CI: −431 to 662). The expectant management arm had significantly higher antenatal costs, whereas the immediate birth arm had significantly higher delivery and neonatal costs. There was large variation between total mean costs by country. Conclusion: This economic evaluation found no evidence that expectant management was more or less costly than immediate birth. Outpatient management may offer opportunities for cost savings for those women with delayed delivery. Tweetable abstract: For women with preterm prelabour rupture of the membranes, the relative benefits and harms of immediate and expectant management should inform counselling as costs are similar. Tweetable abstract: For women with preterm prelabour rupture of the membranes, the relative benefits and harms of immediate and expectant management should inform counselling as costs are similar.